2020
DOI: 10.1080/13669877.2020.1750457
|View full text |Cite
|
Sign up to set email alerts
|

Public acceptance model for siting a repository of radioactive contaminated waste

Abstract: Albrecht, and Bourke 1998). Especially, siting a NIMBY facility concentrates the risk 27 and cost on siting areas while diffusing the benefits outside of the siting areas. Thus, even 28 if they agree that a repository to dispose of harmful waste is necessary, they refuse to 29 build one in their hometown, that is, their backyard. In particular, NIMBY facilities often 30 induce a conflict between siting and non-siting areas. While residents in siting areas suffer 31 damage to their private interests, such as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This indicates a lack of information disclosure and transparency, which are important elements of procedural fairness. In line with our findings, procedural fairness has been found to be associated with acceptance of NIMBY facilities (Kuhn and Ballard 1998 ; Besley 2010 ; Ohtomo et al 2014 ; Takada et al 2022 ) and is an important concern especially for people who oppose these projects (Hirose 2007 ). Comments frequently expressed respondents’ disapproval of disposing of the contaminated soil outside Fukushima Prefecture.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates a lack of information disclosure and transparency, which are important elements of procedural fairness. In line with our findings, procedural fairness has been found to be associated with acceptance of NIMBY facilities (Kuhn and Ballard 1998 ; Besley 2010 ; Ohtomo et al 2014 ; Takada et al 2022 ) and is an important concern especially for people who oppose these projects (Hirose 2007 ). Comments frequently expressed respondents’ disapproval of disposing of the contaminated soil outside Fukushima Prefecture.…”
Section: Discussionsupporting
confidence: 88%
“…Sixth, some studies have shown that the importance of observing procedural justice depends on the individual characteristics of people, such as their personal values (e.g., Esaiasson et al., 2019; Kershaw & Alexander, 2003) and the characteristics of the situation, including levels of uncertainty or threats (e.g., Herian et al., 2012; Ohtomo et al., 2021). However, scholars who study political processes tend to pay little attention to such factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we noted the methods which researchers used to measure procedural justice: direct assessment of procedural justice versus assessment of compliance with procedural justice norms (Research Question 4). In the first case, the researchers asked respondents to evaluate generally how fair or unfair the decision‐making process was (Esaiasson et al., 2019; Ohtomo et al., 2021). In the second case, the researchers asked participants to rate how far a set of norms were respected in political interactions and then calculated an overall index of procedural justice (e.g., Azmi et al., 2016; Badiora, 2020; Hou et al., 2019; Leung et al., 2007; Vainio, 2011; Van Dijke et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have found that benefit perception is an important predictor of public acceptability of NIMBY facilities [ 9 , 29 ]. A significant number of domestic and international scholars have analyzed the impact of perceived justice on the public acceptability of NIMBY facilities, focusing on distributive justice and procedural justice [ 30 ]. Similarly, Batel and Devine‐Wright [ 31 ] found that a lack of justice is a significant reason for community residents opposing wind power plants.…”
Section: Psychological Satisfaction Of Nimbymentioning
confidence: 99%